An Approach of Laser-Induced Breakdown Spectroscopy to Detect Toxic Metals in Crushed Ice Ball. (21st October 2013) - Agrawal, Rahul; Pathak, Ashok Kumar; Rai, Awadhesh Kumar; Rai, Gyanendra Kumar
Abstract : This paper deals the application of laser-induced breakdown spectroscopy (LIBS) to toxic metals used as pigment in crushed ice-ball samples. The present work highlights the advantages of LIBS as in situ, real-time analytical tool for rapid detection of toxic or heavy metals like lead (Pb) and chromium (Cr) and non toxic elements like carbon (C), nitrogen (N), magnesium (Mg), calcium (Ca), sodium (Na), and potassium (K) in crushed ice-ball of different colors (red, green, yellow, pale yellow, and orange) collected from five different areas, with minimal sample preparation. For rapid surveillance of toxic metals we have used multivariate analysis, that is, principal component analysis (PCA) with the LIBS spectral data of ice-ball samples. This study suggests that LIBS coupled with PCA may be an instant diagnostic tool for identification and classification of adulterated and nonadulterated samples.